The Electronic and Cross - Border Trade in The International Scene during The World Pandemia - Giudice Baca, Victor (2021)
The present research has found that peruavian electronic clients grew from 6 millions to 11.8 millions during 2020. It is found also that electronic enterprises in Peru grew four times from 65,800 to 263,000 during 2020. Tourism and traveling fall, have been a common feature in Peru, USA and Spain. It´s surprising that trans - frontier trade of The USA is vigorous with Asia, and China electronic trade with south Corea is quite wide. Spain buys in Europe Personal care products more tan other countries. Inteligent Devises in the world is nowadays bigger tan human beings. 78% of electronic buys are realized vía smartphones.